Management of neuropathic bladder secondary to spina bifida: Twenty years' experience with a conservative approach - Elagami, Hesham; Abbas, Tariq O.; Evans, Kathryn; Murphy, Feilim (Frontiers in Pediatrics, 2022)
Introduction Treatment of neuropathic bladder complicating spina bifida is an ongoing challenge. Although different management strategies and protocols are available in the literature, reliance on expert opinion remains fundamental. A more conservative approach can be utilized, but patients must be closely monitored throughout the management process. The objective of this study was to review the management and outcomes of the neuropathic bladder in spina bifida by appraising long-term bladder and renal function in patients treated at a medical centre utilizing a conservative management style. Methods This is single-centre retrospective review of Urology care for all spina bifida patients 5-19 years of age with a neuropathic bladder who attended follow-ups between April 2000 and April 2020. Identified patients were only included with more than 5 years follow-up. Renal functions, continence, and results of invasive video Urodynamics (IUD) and any surgical interventions were recorded. Results Seventy-one patients (mean age = 10.5 years) were identified after exclusions. Bladder compliance between first and last IUDs increased significantly (p=0.0056). Anticholinergic treatment was started at the first outpatient appointment. Intravesical botulinum toxin injection was the second line treatment in ten patients. 94% of patients had an end fill pressure below 40 cm H2O in their last IUD. 82% were socially continent with or without catheterization at the age of 11.5 years. One patient in the cohort had bladder augmentation. Conclusion The optimal management of neuropathic bladder complicating spina bifida remains controversial. Bladder and renal functional outcomes can be improved with close monitoring and less invasive management.